2007
DOI: 10.1016/j.physa.2007.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Cellular automata for the spreading of technologies in socio-economic systems

Abstract: We introduce an agent-based model for the spreading of technological developments in socio-economic systems where the technology is mainly used for the collaboration/interaction of agents. Agents use products of different technologies to collaborate with each other which induce costs proportional to the difference of technological levels. Additional costs arise when technologies of different providers are used. Agents can adopt technologies and providers of their interacting partners in order to reduce their c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…6 In terms of the possible values of opinions, the opinion dynamics models can be categorized into three main groups: 7 (1) discrete opinion models; (2) continuous opinion models; (3) continuous opinions and discrete actions (CODA) model [12]. 8 These opinion dynamics models, although are not able to precisely predict the real-world observations in some cases, can 9 help us capture the critical factors that govern the opinion evolution and diffusion. 10 In the continuous opinion models, the opinion of each agent ranges within a continuous opinion space (e.g., [0, 1]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In terms of the possible values of opinions, the opinion dynamics models can be categorized into three main groups: 7 (1) discrete opinion models; (2) continuous opinion models; (3) continuous opinions and discrete actions (CODA) model [12]. 8 These opinion dynamics models, although are not able to precisely predict the real-world observations in some cases, can 9 help us capture the critical factors that govern the opinion evolution and diffusion. 10 In the continuous opinion models, the opinion of each agent ranges within a continuous opinion space (e.g., [0, 1]).…”
Section: Introductionmentioning
confidence: 99%
“…Among several different discrete opinion 8 models, we highlight voter model [17,18], Sznajd model [19][20][21], and majority-rule model [22][23][24]. In the voter model, each 9 agent is randomly chosen to adopt the opinion of one of his neighbors, whereas in the Sznajd model two agents with the Q3 10 same opinion persuade their neighbors to accept their opinion. The agents in the majority-rule model update their opinions 11 by following the local majority rule.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Spreading-Successful technologies spread over the system, resulting in an overall technological progress. The understanding of the technological progress of socioeconomic systems requires the analysis of the complex dynamics of several levels from the interaction of firms investing in research and doing production [5][6][7], through the emergence of new ideas captured by the network of patents [8], down to the level of individuals that use the newly developed products [9][10][11][12]. A crucial element of the diffusion of technological advancements is the spreading of information about the existence and advantages of the newly developed technology.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion of innovations also involves * feri@dtp.atomki.hu components analogous to opinion spreading and consensus formation [9][10][11][12][16][17][18][19][20][21][22][23][24][25][26][27]. As an example, telecommunication technologies can be mentioned, where the usage of a technology assumes that the communication partners are approximately at the same technological level [1,[9][10][11][12]19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It has even been suggested that cellular automata and related systems are candidates for expressing fundamental laws of nature, in contrast to traditional mathematical approaches based on differential equations [34]. At a different level, the relevance of such idealized systems to real-world applications is illustrated by a cellular-automaton model for the adoption of a new technology in an economy [24].…”
Section: Introductionmentioning
confidence: 99%